Stúdium lokálnych anestetík. CX. Príprava, aktivita a rozdeĺovacie koeficienty pyrolidínoetylesterov 2-, 3-a 4-alkoxysubstituovaných kyselín fenylkarbámových - Cizmárik, J; Polásek, E; Svec, P; Racanská, E (Ceskoslovenska farmacie, 1993)
By pyrrolidinoethylalcohol addition on 2-, 3- and 4-alkoxy-substituted phenylisocyanate in non-aqueous toluene medium a series of 30 compounds of the type Pyrrolidinoethylesters of 2-, 3- and 4-alkoxy substituted phenylcarmabim acids were prepared. Pharmacological evaluation results shown after comparing with cocaine and procaine standards that these compounds have a higher index of effectiveness in both types of local anaesthesia. The maximum effectiveness of surface anaesthesia shows Pyrrolidinoethylester of 2-octyloxy phenylcarbamic acid which is 204-times more effective as cocaine. The maximum effectiveness of infiltration anaesthesis shows Pyrrolidinoethylester of 2-heptyloxy phenylcarbamic acid which is 66-times more effective as procaine. Prepared compounds are more effective in the case of surface anaesthesia as in the case of infiltration anaesthesia and they have comparatively high values of partition coefficients P' and P' cal. Comparison of prepared compounds effectiveness and analogic piperidinoethylesters shows that in more cases they are either equal or nearer effective. The values of their P' and P' cal correlate with these results.
Keywords: Carbamates; myši; karbamáty; pyrrolidiny; Pyrrolidines; zvířata; Anesthetics, Local; Mice; anestetika lokální; Animals